A Flame Detection Method Based on Fusion Feature and SVM for Substation Inspection. (August 2020) - Deng, Jieqing; Wei, Chao; Chen, Guang; Xu, Liang; Zhu, Bo
Abstract: For the safety inspection of substation, this paper proposes a flame image detection method based on the combination of fusion feature and support vector machine (SVM). Firstly, the suspected flame area is detected by motion detection and flame color model. Then, four features of B-channel color variation coefficient, roughness, flicker frequency and flame area change rate are extracted. Finally, four features are sent to SVM to learn the flame classifier and used in video flame detection. The experimental results show that the proposed method can effectively identify the flame.